New Strategy of Marketing Mix Model to Enhance Hotel Revenue - Ni Luh Yuni Widyasari; Ni Nyoman Triyuni; I Nyoman Rajin Aryana (Jurnal Sains Terapan Pariwisata, 2021)
The purpose of this research is to determine the marketing strategy implementation and the most suitable marketing strategy that can be applied in increasing revenue at Wyndham Garden Kuta Beach Bali. The research data was collected through questionnaires, participation observation, interviews, and documentation and performed by qualitative descriptive analysis, Internal factors, External factors, IE matrix analysis, SWOT matrix, and QSPM. This research used a marketing mix of 12 Ps (internal-external). Wyndham Garden Kuta Beach Bali is in cell five of the Internal-External matrix with total weighting score of 2,92 on internal factors and a score of 2,96 on external factors. The position in cell five shows Wyndham Garden Kuta Beach Bali is in growth (concentration through horizontal integration) or stability (there is no change).